A locally advanced pancreatic body cancer presenting common bile duct invasion resected via distal pancreatectomy after gemcitabine plus nab-paclitaxel chemotherapy: A case report. (March 2022) - Kawasaki, Hiroshi; Hoshikawa, Mayumi; Kyoden, Yusuke; Iijima, Tatsuo; Kojima, Hiroshi; Yamamoto, Junji
Abstract: Introduction: The locally advanced pancreatic cancer has been steadily recognized as a potentially curable disease by a combination of chemotherapy and surgery. The remarkable effect of advanced chemotherapy would help surgeons do a function-preserving operation for advanced pancreatic cancer. Presentation of case: A 73-year-old woman presenting with obstructive jaundice was diagnosed to have a 3-cm pancreatic body cancer invading the celiac axis (CA), superior mesenteric artery (SMA), portal/splenic vein confluence, and the common bile duct (CBD). A plastic internal stent tube was placed endoscopically. After 11 cycles (231 days) of a weekly doublet chemotherapy with 1000 mg/m 2 of gemcitabine and 125 mg/m 2 of albumin-bound paclitaxel, the tumor shrunk based on imaging done every four months during chemotherapy, with residual periarterial high-density area around CA and proximal SMA and the patient was referred for surgery. During the operation, the absence of cancer cells was confirmed at (1) the origin of the proper hepatic artery, gastroduodenal artery and the left gastric artery, and (2) pancreatic cut stump along the right border of the portal vein; thus, distal pancreatectomy with coeliac axis resection was done. The patient had postoperative adjuvant chemotherapy with 100 mg/day of tegafur/gimeracil/oteracil for half a year and is currently alive and well, without signs of recurrence and diabetes mellitus a year after surgery. Discussion: Although surgical techniques aimed at local radicality are important, especially for conversion surgery for locally advanced pancreatic cancer, surgeons should consider the balance between radicality, safety, and functional preservation of surgery. Highlights: A locally advanced pancreatic cancer has been curable by chemotherapy and surgery. The arterial invasion by imaging diagnostics is sometimes released by chemotherapy. The common bile duct invasion was dissolved after chemotherapy. The effect of chemotherapy would help surgeons do a function-preserving operation.